Cerebrospinal Fluid TNF-α and Orexin in Patients With Parkinson's Disease and Rapid Eye Movement Sleep Behavior Disorder - Yuan, Yuan; Zhang, Yimeng; Cheng, Yueyang; Hou, Yue; Huang, Zhaoyang; Ma, Jinghong; Li, Ning; Zhan, Shuqin (Frontiers in Neurology, 2022)
Background: Parkinson's disease (PD) pathological changes begin before motor symptoms appear. Rapid eye movement sleep behavior disorder (RBD) has the highest specificity and predictive value of any marker of prodromal PD. Tumor necrosis factor α (TNF-α) plays a part in the pathology of PD and disease conversion in isolated RBD (iRBD). TNF can also directly impair the hypocretin system in mice in vivo. As a result, we intend to investigate the effect of TNF-α on orexin levels in PD patients with RBD. Method: Participants were recruited from the Department of Neurology of Xuanwu Hospital, Capital Medical University to engage in assessments on motor symptoms, sleep, cognition, etc. Then we collected blood and cerebrospinal fluid of all patients and ten controls’ cerebrospinal fluid. The levels of TNF-α in the serum and cerebrospinal fluid, as well as the level of orexin in the cerebrospinal fluid, were measured in the patients. Results: The difference in TNF- levels in cerebrospinal fluid and serum between the three groups were not statistically significant. The levels of orexin in the three groups were not significantly lower than in the control group. UPDRS-III scores were significantly higher in the PD+RBD and PD-RBD groups than in the iRBD group. There was no statistically significant difference in H-Y stages, PSQI, or ESS scores between the PD+RBD and PD-RBD groups. Conclusion: Our findings suggest that TNF-α may not have a significant effect on the orexinergic system in patients with Parkinson's disease and iRBD. As a result, it is necessary to investigate the changes in TNF-α and orexin levels in different disease stages and to enlarge the sample size to determine whether TNF-α affects the function of the orexin system, which may be related to the occurrence of RBD and disease progression in Parkinson's disease.